2020
DOI: 10.1002/cncr.32960
|View full text |Cite
|
Sign up to set email alerts
|

Molecular profiling and analysis of genetic aberrations aimed at identifying potential therapeutic targets in fibrolamellar carcinoma of the liver

Abstract: Background Fibrolamellar carcinoma (FLC) is a rare primary liver cancer of young adults. A functional chimeric transcript resulting from the in‐frame fusion of the DNAJ homolog, subfamily B, member 1 (DNAJB1), and the catalytic subunit of protein kinase A (PRKACA) genes on chromosome 19 is believed to be unique in FLC, with a possible role in pathogenesis, yet with no established therapeutic value. The objective of the current study was to understand the molecular landscape of FLC and to identify potential nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…However, recent studies have reported that this fusion gene is also detected in other pancreatic and biliary tumors 14 , whereas FLHCC without the fusion gene has also been reported. 15 We were not able to test this case for the DNAJB1-PRKACA alteration; however, the pathological features were typical of FLHCC and sufficient for its diagnosis. Further studies are needed to explain the roles of DNAJB1-PRKACA and other genes in the pathogenesis of FLHCC.…”
Section: Discussionmentioning
confidence: 82%
“…However, recent studies have reported that this fusion gene is also detected in other pancreatic and biliary tumors 14 , whereas FLHCC without the fusion gene has also been reported. 15 We were not able to test this case for the DNAJB1-PRKACA alteration; however, the pathological features were typical of FLHCC and sufficient for its diagnosis. Further studies are needed to explain the roles of DNAJB1-PRKACA and other genes in the pathogenesis of FLHCC.…”
Section: Discussionmentioning
confidence: 82%
“…However, another possible scenario is the need of additional mutation(s) to complement/synergize with the chimeric fusion for the appearance of a more cancer-like phenotype 76 , possibly through a similar hepatocyte transdifferentiation event as observed for BAP1 KO ;PRKAR2A KO . Indeed, various genomic studies have identified additional mutations in some fusion-driven FLC tumors, such as those in TERT, CTNNB1 , or MUC4 6 , 77 . Finally, cell-to-cell contact with different liver cell types as well as changes in the niche environment or organ crosstalk may be important to ultimately drive cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, the small part of DNAJ1B fused to PKA in FLC tumors also contributes to tumor development in mice [27], an observation supported by biochemical and structural studies [31][32][33][34][35][36]. Few additional alterations have been found in the genome of FLC tumors, but accumulating evidence suggests a role for telomerase activity, MAPK signaling, and WNT signaling [26,27,35,[37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 96%